I got my differential equation down to this and now only need to solve for y, but how do I do it?
(e^y)/(e^y+1) = Ce^(0.5x^2), where C is a constant.
(e^y)/(e^y+1) = Ce^(0.5x^2), where C is a constant.
-
e^y / (1 + e^y) = Ce^((1/2) * x^2) <==== long division
. . . . . 1
. . . . . _____
e^y + 1I e^y
. . . . .-
. . . . . .e^y + 1
. . . . . _______
. . . . . 0 - 1
1 - 1/e^y
1 - 1/e^y = Ce^((1/2) * x^2)
1 - Ce^((1/2) * x^2) = 1/e^y
e^y = 1/(1 - Ce^((1/2) * x^2))
ln( e^y ) = ln( 1 / (Ce^((1/2) * x^2) )
y = ln( 1 ) - ln(Ce^((1/2) * x^2))
y = 0 - ln(Ce^((1/2) * x^2))
y = - ln(Ce^((1/2) * x^2))
. . . . . 1
. . . . . _____
e^y + 1I e^y
. . . . .-
. . . . . .e^y + 1
. . . . . _______
. . . . . 0 - 1
1 - 1/e^y
1 - 1/e^y = Ce^((1/2) * x^2)
1 - Ce^((1/2) * x^2) = 1/e^y
e^y = 1/(1 - Ce^((1/2) * x^2))
ln( e^y ) = ln( 1 / (Ce^((1/2) * x^2) )
y = ln( 1 ) - ln(Ce^((1/2) * x^2))
y = 0 - ln(Ce^((1/2) * x^2))
y = - ln(Ce^((1/2) * x^2))
-
solve(e^y/(e^y+1) = C*e^(0.5*x^2), y)
y = (.5*(2.*ln( - C/( - 1. + C*exp(0.5*x^2))) + x^2))
y = (.5*(2.*ln( - C/( - 1. + C*exp(0.5*x^2))) + x^2))